2003
DOI: 10.1016/s1053-8119(03)00235-0
|View full text |Cite
|
Sign up to set email alerts
|

Human motor cortex activity during mental rotation

Abstract: The functional role of human premotor and primary motor cortex during mental rotation has been studied using functional MRI at 3 T. Fourteen young, male subjects performed a mental rotation task in which they had to decide whether two visually presented cubes could be identical. Exploratory Fuzzy Cluster Analysis was applied to identify brain regions with stimulus-related time courses. This revealed one dominant cluster which included the parietal cortex, premotor cortex, and dorsolateral prefrontal cortex tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
2
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 32 publications
4
21
2
3
Order By: Relevance
“…Results gained by different long and short versions of the test can be compared through the estimation of person parameters on the basis of the difficulty parameters of the presented items. The test has already been used for measurement of mental rotation within different international published studies (Weiss et al 2003;Windischberger et al 2003). Gittler (1990) reports consistent and robust gender differences for the probability of finding the solution for every given item within the 3DC, which conforms with the theoretical implications of the scaling.…”
Section: Methodsmentioning
confidence: 81%
“…Results gained by different long and short versions of the test can be compared through the estimation of person parameters on the basis of the difficulty parameters of the presented items. The test has already been used for measurement of mental rotation within different international published studies (Weiss et al 2003;Windischberger et al 2003). Gittler (1990) reports consistent and robust gender differences for the probability of finding the solution for every given item within the 3DC, which conforms with the theoretical implications of the scaling.…”
Section: Methodsmentioning
confidence: 81%
“…Windischberger et al (2003) found that M1 was activated in a mental rotation task, but attributed the activation to button press responses and thus is simply an artifact, rather than the being associated with mental rotation task itself. Cohen et al (1996) did not find M1 activation due to the mental rotation task, and instead suggest that it is a visual/spatial imagery task, rather than a motor imagery task.…”
Section: Mental Rotationmentioning
confidence: 99%
“…This comes from the growing body of evidence from functional brain-imaging studies implicating the SMC (along with other brain areas, including the intraparietal sulcus, the right superior parietal lobe and the ventrolateral prefrontal cortex) in abstract mental computations supporting visuospatial transformation in tasks like mental rotation (in which observers judge shape equivalence or mirror reflection across changes in visual-stimulus orientation) [2][3][4][5][6] . Of interest also is that visuo-spatial processing in tasks like mental rotation has been shown to be impaired in (at least some) patients with Parkinson's disease [7][8][9] , the underlying pathology of which, as discussed by Nachev et al, is known to affect the SMC -for example, via the loss of pyramidal neurons in the pre-SMA and via dopamine depletion in the nigro-striatal pathways linking the basal ganglia and the pre-motor cortex 10 .…”
mentioning
confidence: 99%
“…Similarly, the determination of stimulus orientation in space, and of the angular transformation required to remap feature locations from one coordinate system to another, can also be assumed to involve calculation of a vector. According to this hypothesis, regions of the SMC (possibly the pre-SMA 2,4 ) may be functionally involved in the computation of abstract vector transformations such as those that have been associated with neuronal-population vector transformations underlying the planning of movement 14 and with visuo-spatial image normalization during mental rotation 2,15 . This characterization proposes a relatively abstract computational role within the SMC beyond the traditional view.…”
mentioning
confidence: 99%